Intelligent Framework for Regional Tourism Ecological Efficiency Evaluation under High-Quality Development with Single-Valued Neutrosophic Information - Xiaoying Liu (Neutrosophic Sets and Systems)
The evaluation of regional tourism ecological efficiency (RTEE) under high-quality development aims to measure how the tourism industry promotes economic growth while minimizing resource consumption and environmental impact. By analyzing economic output per unit of carbon emissions, it assesses the sustainability and environmental performance of the tourism sector. This evaluation method considers resource utilization, energy efficiency, and ecological protection, helping decision-makers optimize tourism development models, achieve a balance between economic and ecological benefits, and promote the transition of tourism towards a low-carbon, green, and high-quality direction. The RTEE evaluation under high-quality development is MADM. The single-valued neutrosophic number generalized power geometric BM (SVNNGPGBM) technique is put forward and MADM decision techniques are put forward in line with SVNNGPGBM technique and power geometric (PG) technique. Finally, numerical example about RTEE evaluation under high-quality development and comparative analysis was put forward the SVNNGPGBM technique.